A Atitude Relacional na Teoria e Prática da Terapia Gestalt.: The Relational Attitude in Gestalt Therapy Theory and Practice. - Yontef, Gary (IGT na Rede ISSN 1807-2526, 2007)
Neste artigo publicado originalmente no International Gestalt Journal no ano de 2002, Gary Yontef revê cada um dos três fundamentais princípios filosóficos da gestalt terapia: a fenomenologia existencial, a teoria de campo e o existencialismo dialógico e discute as práticas e atitudes da Gestalt Terapia que são incompatíveis com estes princípios. Gestalt therapy theory is relational in its core, al-though some talk and practice of gestalt therapy is not consis-tent with the principles. This paper reviews core relational philosophical principles of gestalt therapy: existential phe-nomenology, field theory, and dialogic existentialism. The im-plications for practice are explored. Practices and attitudes about gestalt therapy that are inconsistent with these principles are discussed. The article studies the triggering and treatment of shame in gestalt therapy and gestalt training. The article clarifies what relational gestalt therapy is and what it is not.